Neuropeptide Y receptor interactions regulate its mitogenic activity. (February 2019) - Czarnecka, Magdalena; Lu, Congyi; Pons, Jennifer; Maheswaran, Induja; Ciborowski, Pawel; Zhang, Lihua; Cheema, Amrita; Kitlinska, Joanna
Abstract: Neuropeptide Y (NPY) is a multifunctional neurotransmitter acting via G protein-coupled receptors - Y1R, Y2R and Y5R. NPY activities, such as its proliferative effects, are mediated by multiple receptors, which have the ability to dimerize. However, the role of this receptor interplay in NPY functions remains unclear. The goal of the current study was to identify NPY receptor interactions, focusing on the ligand-binding fraction, and determine their impact on the mitogenic activity of the peptide. Y1R, Y2R and Y5R expressed in CHO-K1 cells formed homodimers detectable on the cell surface by cross-linking. Moreover, Y1R and Y5R heterodimerized, while no Y2R/Y5R heterodimers were detected. Nevertheless, Y5R failed to block internalization of its cognate receptor in both Y1R/Y5R and Y2R/Y5R transfectants, indicating Y5R transactivation upon stimulation of the co-expressed receptor. These receptor interactions correlated with an augmented mitogenic response to NPY. In Y1R/Y5R and Y2R/Y5R transfectants, the proliferative response started at picomolar NPY concentrations, while nanomolar concentrations were needed to trigger proliferation in cells transfected with single receptors. Thus, our data identify direct and indirect heterotypic NPY receptor interactions as the mechanism amplifying its activity. Understanding these processes is crucial for the design of treatments targeting the NPY system. Highlights: NPY receptors form homodimers and heterodimers. Co-expression of heterotypic NPY receptors enables their reciprocal transactivation. Receptor transactivation can occur independently of heterodimer formation. Heterotypic NPY receptor interactions increase cell sensitivity to its low levels. Targeting multiple NPY receptors may improve therapies exploiting NPY system.